2001
DOI: 10.1177/000313480106700510
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Artery Aneurysms: Experience in a Tertiary-Care Center

Abstract: Visceral artery aneurysms (VAAs) often rupture and cause serious morbidity or death. The purpose of this study was to identify conditions associated with VAA in a series of 30 patients treated at our institution from 1988 through 1998. Demographics, types of aneurysms, associated conditions, diagnoses, treatments, and outcomes were recorded and analyzed. Thirty patients (16 men and 14 women) with VAA were identified. The arteries involved were splenic (eight), renal (ten), hepatic (nine), hypogastric (one), ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(4 citation statements)
references
References 31 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…4 ), which is a relatively rare condition. Its reported prevalence is approximately 1% in the total population, and it is found in 0.01–0.2% of autopsy cases, most of which are detected following rupture [ 30 , 31 ]. Although the increased risk of bleeding could be related to endothelial dysfunction, coagulopathy or disseminated intravascular coagulation in COVID-19, the risk of bleeding in patients with mild COVID-19 was not reported to increase [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…4 ), which is a relatively rare condition. Its reported prevalence is approximately 1% in the total population, and it is found in 0.01–0.2% of autopsy cases, most of which are detected following rupture [ 30 , 31 ]. Although the increased risk of bleeding could be related to endothelial dysfunction, coagulopathy or disseminated intravascular coagulation in COVID-19, the risk of bleeding in patients with mild COVID-19 was not reported to increase [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The splenic artery is the most commonly involved. Gastroduodenal artery pseudoaneurysm is the second most commonly encountered, even though its involvement is very rare overall [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal VAAs have an incidence of about 0.01 to 2%. 3 SAA is the most frequent among them, occurring in about 50 to 75% of the reported VAAs. 3,4 The risk factors for SAA include portal hypertension, female hormones such as estrogen, and severe flexion.…”
Section: Discussionmentioning
confidence: 99%
“…3 SAA is the most frequent among them, occurring in about 50 to 75% of the reported VAAs. 3,4 The risk factors for SAA include portal hypertension, female hormones such as estrogen, and severe flexion. 5 It was observed that SAAs are four times more frequent in women.…”
Section: Discussionmentioning
confidence: 99%